Analisis Pengaruh Komposisi Biomassa terhadap Karakteristik Pembakaran dan Stabilitas Energi Berbasis Data: Analisis Bibliometrik - Zharif, Erza Arkan; Abdillah, Akbar; Praba, Lindi Cistia; Silmy, Muhammad Ashbar As; Dharmawangsa, Rafa Aditya; Septiawan, Bani; Lubis, Putri Bintang (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The growing global demand for energy and the depletion of fossil fuel resources have accelerated the transition toward sustainable energy systems. Biomass has emerged as an important renewable energy source due to its abundance, carbon-neutral characteristics, and relatively stable energy supply. However, biomass has complex chemical compositions such as cellulose, hemicellulose, lignin, moisture, and ash, which significantly affect combustion characteristics and energy performance. This study analyzes the relationship between biomass composition, combustion characteristics, and energy stability using a bibliometric approach. A dataset of 3,521 scientific publications from the Scopus database (2021–2026) was analyzed using VOSviewer and Bibliometrix. The results show increasing research trends in biomass combustion and thermochemical processes. However, the integration between biomass composition and energy stability remains limited, indicating important opportunities for future interdisciplinary research in biomass-based energy systems.